(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: In healthy population, spatial parameters of gait such as stride length and step length arefrequently linked with gait cycle but can be obstructive, time taking and difficult to measure. This study is tocheck theefficacy of kinect azure for evaluating of spatial parameters of gait in normal healthy population.Kinect is accurate, unobstructive, low cost clinical gait analysis systems have many uses like diagnosis,monitoring, management and rehabilitation.Method: The research has been designed as an observational study.The total of 132 participants will betaken from AVBRH, sawangi Meghe for study as per exclusion and inclusion criteria.With intervention thespan of the study will be 6 months. It holds single period, concurrent validity evaluation comparing spatialgait parameters derived from the Kinect system.Discussion: This study protocol aims to assess the efficacy of Microsoft kinect azure for evaluation ofspatial parameters of gait.The study’s expected outcome will concentrate on the evaluation of the usabilityof kinect to assess spatial gait on healthy individuals.